Changes in the hydrological characteristics of Cauvery river draining the eastern side of southern Western Ghats, India. Issue 2 (2nd April 2020) - Sreelash, K.; Mathew, Merin Mariam; Nisha, N.; Arulbalaji, P.; Bindu, A. G.; Sharma, Rajat Kumar
ABSTRACT: The changes in land use and regional climate together with human interventions affect the hydrological processes, resulting in the spatial and temporal alterations of surface and subsurface flow processes. Both climate and land surface change have adverse implications on the natural hydrological system in terms of variation in the run-off regime, surface storage, evapotranspiration, subsurface ﬂow and infiltration, thereby affecting the hydrology of the river basin as a whole. Even though several studies worldwide have attempted to address the influence of climate change, land-use change and human activities on the hydrology of river basins, either as a whole or limited to a few components of the hydrological cycle, limited attention has been given to study the hydrological changes in the river basins of arid and semi-arid tropics, which are essentially fed by precipitation. The objective of the study is to analyse the changes in hydrological characteristics of the Cauvery river basin, a semi-arid river basin in South India. The changes in the hydrology of the Cauvery river basin are studied by analysing the trends in hydro-meteorological parameters using Mann-Kendall trend tests and Sen's estimator of the slope. The results showed that the changes in the volume of rainfall and the number of rainy days significantly affect the overall hydrological regime of the river basin. The analysis of annual and seasonal rainfall over the Cauvery river basin showed a decreasing trend in the middle Cauvery basin. A declining trend in the number of rainfall events was also observed in the middle Cauvery region. The effect of decreasing trend in the volume of rainfall and number of rainy days is evident from the decreasing trends in the streamflow of the main channel and tributaries of the Cauvery river. The regions of increase in evapotranspiration showed a significant correlation with the regions which exhibited a decline in groundwater level.